Synchronization Of Authority To Eradicate Criminal Acts Of Corruption According To Law 31 Of 1999 Concerning The Eradication Of Criminal Acts Of Corruption Handled By The Corruption Eradication Committee (KPK), The Prosecutor's Office, And The Republic O - Mona Fidelia Manurung; M. Arafat Hermana; Ferawati Royani (JURNAL HUKUM SEHASEN, 2026)
Corruption is a systemic problem that has become deeply rooted in Indonesia's national life, with multidimensional impacts that harm state finances, undermine democracy, and hinder development. Efforts to eradicate corruption are carried out by three law enforcement institutions: the Corruption Eradication Commission (KPK), the Attorney General's Office of the Republic of Indonesia, and the National Police of the Republic of Indonesia, each with authority based on statutory regulations. This study aims to analyze the synchronization of the authority of these three institutions in implementing corruption eradication in accordance with Law Number 31 of 1999 concerning the Eradication of Corruption Crimes (as amended) and to evaluate the impact of Law Number 19 of 2019 on their performance. The research method used is normative legal research with statutory, case, and historical approaches, as well as qualitative analysis of secondary data in the form of primary, secondary, and tertiary legal materials. The results show that normatively, regulations on corruption eradication are coherent, applying the principle of lex specialis derogat legi generali. The KPK has special authority to handle corruption cases involving law enforcement officials or state administrators, cases that receive public attention, and/or those involving state losses of at least IDR 1 billion. Meanwhile, the Attorney General's Office and the National Police handle corruption cases that do not meet these qualifications, with the Attorney General's Office responsible for investigation and prosecution, and the National Police tasked with inquiry and investigation. However, in practice, there is a lack of synchronization marked by overlapping authority, differences in interpretation of regulations, and horizontal conflicts between institutions. The existence of limiting boundaries regarding the authority of each institution (National Police, Attorney General's Office, and KPK) in handling corruption crimes is intended to ensure that relations between law enforcement institutions do not lead to monopolization or overstepping of each other's duties.